Hedonic Motivation, Price Value, and Habits in E-Wallet Adoption: Extended UTAUT2 Testing on Generation Z Consumers in Manado - Modaso, Paske V.; Dalughu, Meyliza H.; Wua, Injilia W.G (Journal of Management and Administration Provision, 2025)
This study explores the role of Hedonic Motivation, Price Value, and Habit in predicting e-wallet adoption among Generation Z consumers in Manado City. Employing a quantitative approach with an explanatory survey design, data were collected from 100 Gen Z e-wallet users in Manado via an online questionnaire, then analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The findings indicate that all three variables positively and significantly influence e-wallet adoption. Habit emerged as the most dominant predictor (β=0.457), followed by Price Value (β=0.321), and Hedonic Motivation (β=0.189). The model explains 68.5% of the variance in e-wallet adoption (R2=0.685) and demonstrates strong predictive relevance (Q2=0.452). Practical implications suggest that e-wallet service providers and businesses in Manado should reinforce usage habits, offer competitive price value, and enhance hedonic experiences to foster sustained adoption among Gen Z. Although limited to a Gen Z sample in Manado, this research provides new empirical insights into intrinsic factors influencing consumer technology adoption.